The Power of Negative Disposition: An Examination of Trait and State Negative Affect With OCBI and OCBO. Issue 6 (December 2019) - Geiger, Mark; Lee, Jeong-Yeon; Geiger, Mingang K.
The authors developed and tested a two-by-two framework that identifies the strength of relationships between facets of negative affect (trait and state) and facets of organizational citizenship behavior (OCBI and OCBO). The framework is based on a stream of research concerned with dispositional- and situational-based predictors of OCB and is complemented with the phenomenon of social exchange spillover. Hypotheses were developed and tested using meta-analytic data to provide an authoritative perspective on the relationships of interest. The results largely support the proposed framework and suggest the strongest relationships are those between trait negative affect and OCBO, whereas the weakest relationships are those between state negative affect and OCBI. The authors discuss implications for research and practice concerning relationships between negative affect and OCB.